Negotiating Religious Authority: Digital Da’wah and the Transformation of Islamic Law Interpretation Among Generation Z - Rahajeng Mar’atus Sholehah; Yustinina Rachelia Hariani; Qisthi Efridita (Al-Fiqh: Journal of Contemporary Islamic Law, 2026)
The purpose of this research is to understand the impact of digital da'wah on the understanding and acceptance of Islamic law among Generation Z. The background of this research is the major shift in how religion is conveyed through digital platforms, leading to a shift in authority to non-institutional figures such as social media influencers. In addition, the younger generation is more exposed to diverse views of Islamic law without a central authority. This study uses a qualitative, dual-case study design, collecting data through in-depth interviews and participatory observation of social media activities. The research findings show that platforms such as YouTube, TikTok, and Instagram have become the primary channels for proselytizing among Generation Z, who prefer flexible, interactive, and accessible content. However, the diversity and conflict of views on Islamic law in the digital world create confusion about halal and haram. This research also highlights the need for standardization and supervision in digital da'wah to maintain the consistency of Islamic teachings. This research's contribution offers insights into the changing nature of religious authority in the digital age, as well as recommendations for religious institutions to use social media more effectively and provide authentic guidance.